Tingkat Pengetahuan dan Partisipasi Masyarakat terhadap Pelaksanaan Aplikasi Salinmas (Sampah Online Banyumas) dalam Mengatasi Permasalahan Sampah - Marwanti, Ryan; Aji, Ananto (Badan Pengembang Konservasi UNNES, 2020)
Research objectives are: Describe the implementation of the SalinMas Application in overcoming the problem of waste in Sokanegara Village and Kedungwuluh Village, Know the level of community participation regarding the implementation of the SalinMas Application in Sokanegara Village and Kedungwuluh Village, Know the level of community participation towards the implementation of the SalinMas Application in Sokanegara Village and Kedungwuluh Village, Analyzing the constrains in the implementation of the SalinMas Application in Sokanegara Village and Kedungwuluh Village. The population in this study were all households in each community unit that had implemented the SalinMas Application (Sokanegara Village and Kedungwuluh Village) with 390 houses. The sample was determined using purposive sampling by taking 15% of the population that is as many as 58 samples. The variables studied were community knowledge, community participation, and obstacles in the implementation of the SalinMas Application. Data collection techniques using the method of observation, test, questionnaires, interviews, and documentation. The data analysis technique uses descriptive percentages.Ã‚Â The results shows that the implementation of the SalinMas Application from the initial stage to the present was carried out very well despite the contraints in its implementation. The level of public knowledge on the implementation of the SalinMas Application is included in the very high category with an average score of 90,44% (Sokanegara Village) and 87,87% (Kedungwuluh Village). In addition, the level of community participation in the implementation of the SalinMas application is also high with a proportion of 78,10% (Sokanegara Village) and 81,57% (Kedungwuluh Village). The obstacles faced in implementing the SalinMas application can be seen in terms of operational costs, cooperation with the bank, complaints from KSM, and waste pick-up processes. Suggestions are addressed to local goverments so that the government fulfil and complete infrastructure, cooperation with the (BKK), and improve road access to PDU. In addition, suggestions are also addressed of the public to increase the level of participation in government assessments, and evaluate the implementation of the SalinMas application for at least one month.